An efficient method for approximating resonance curves of weakly-damped nonlinear mechanical systems. (June 2016) - Förster, Alwin; Krack, Malte
Highlights: A frequency domain method for computing forced resonance curves is developed. The method exploits the phase resonance hypothesis for nonlinear systems. Superior computational efficiency, while retaining reasonable range of applicability. Successful validation for two-DOF oscillator and bladed disk with shroud contact. Abstract: A method is presented for tracing the locus of a specific peak in the frequency response under variation of a parameter. It is applicable to periodic, steady-state vibrations of harmonically forced nonlinear mechanical systems. It operates in the frequency domain and its central idea is to assume a constant phase lag between forcing and response. The method is validated for a two-degree-of-freedom oscillator with cubic spring and a bladed disk with shroud contact. The method provides superior computational efficiency, but is limited to weakly-damped systems. Finally, the capability to reveal isolated solution branches is highlighted.